Clinical and Surgical Predictors of Complications Following Surgery for the Treatment of Cervical Spondylotic Myelopathy: Results From the Multicenter, Prospective AOSpine International Study of 479 Patients. Issue 1 (July 2016) - Tetreault, Lindsay; Tan, Gamaliel; Kopjar, Branko; Côté, Pierre; Arnold, Paul; Nugaeva, Natalia; Barbagallo, Giuseppe; Fehlings, Michael G.
Abstract : BACKGROUND: Surgery for cervical spondylotic myelopathy (CSM) is generally safe and effective. Nonetheless, complications occur in 11% to 38% of patients. Knowledge of important predictors of complications will help clinicians identify high-risk patients and institute prevention and management strategies. OBJECTIVE: To identify clinical and surgical predictors of perioperative complications in CSM patients. METHODS: Four hundred seventy-nine surgical CSM patients were enrolled in the prospective CSM-International study at 16 sites. A panel of physicians reviewed all adverse events and classified each as related or unrelated to surgery. Univariate analyses were performed to determine differences between patients who experienced a perioperative complication and those who did not. A complication prediction rule was developed using multiple logistic regression. RESULTS: Seventy-eight patients experienced 89 perioperative complications (16.25%). On univariate analysis, the major clinical risk factors were ossification of the posterior longitudinal ligament (OPLL) ( P = .055), number of comorbidities ( P = .002), comorbidity score ( P = .006), diabetes mellitus ( P = .001), and coexisting gastrointestinal ( P = .039) and cardiovascular ( P = .046) disorders. Patients undergoing a 2-stage surgery ( P = .002) and those with a longer operative duration ( P = .001) were at greater risk of perioperative complications. A final prediction model consisted of diabetes mellitus (odds ratio [OR] = 1.96, P = .060), number of comorbidities (OR = 1.20, P = .069), operative duration (OR = 1.07, P = .002), and OPLL (OR = 1.75, P = .040). CONCLUSION: Surgical CSM patients have a higher risk of perioperative complications if they have a greater number of comorbidities, coexisting diabetes mellitus, OPLL, and a longer operative duration. Surgeons can use this information to discuss the risks and benefits of surgery with patients, to plan case-specific preventive strategies, and to ensure appropriate management in the perioperative period. ABBREVIATIONS: BMI, body mass index CSM, cervical spondylotic myelopathy mJOA, modified Japanese Orthopaedic Association OPLL, ossification of the posterior longitudinal ligament